2018
DOI: 10.1016/j.bbadis.2017.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Short-term fructose ingestion affects the brain independently from establishment of metabolic syndrome

Abstract: Chronic fructose ingestion is linked to the global epidemic of metabolic syndrome (MetS), and poses a serious threat to brain function. We asked whether a short period (one week) of fructose ingestion potentially insufficient to establish peripheral metabolic disorder could impact brain function. We report that the fructose treatment had no effect on liver/body weight ratio, weight gain, glucose tolerance and insulin sensitivity, was sufficient to reduce several aspects of hippocampal plasticity. Fructose cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 67 publications
1
23
0
Order By: Relevance
“…Increased fructose ingestion correlates with the development of metabolic diseases such as obesity, insulin resistance, T2DM, nonalcoholic fatty liver disease, hypertension, hyperuricemia, and dyslipidemia [ 90 , 93 , 94 ]. Furthermore, results from animal studies suggest that high fructose intake may be linked to cognitive decline derived from insulin resistance, reduced neurogenesis, mitochondrial dysfunction, and a reduction of hippocampal plasticity [ 89 , 90 , 93 , 95 , 96 , 97 , 98 ]. Epidemiological studies have also suggested an association between the consumption of a Western diet (high in saturated fats and added sugars) with cognitive dysfunction in humans [ 99 , 100 ].…”
Section: Fructose Transporters In Choroid Plexus Epithelial Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased fructose ingestion correlates with the development of metabolic diseases such as obesity, insulin resistance, T2DM, nonalcoholic fatty liver disease, hypertension, hyperuricemia, and dyslipidemia [ 90 , 93 , 94 ]. Furthermore, results from animal studies suggest that high fructose intake may be linked to cognitive decline derived from insulin resistance, reduced neurogenesis, mitochondrial dysfunction, and a reduction of hippocampal plasticity [ 89 , 90 , 93 , 95 , 96 , 97 , 98 ]. Epidemiological studies have also suggested an association between the consumption of a Western diet (high in saturated fats and added sugars) with cognitive dysfunction in humans [ 99 , 100 ].…”
Section: Fructose Transporters In Choroid Plexus Epithelial Cellsmentioning
confidence: 99%
“…In the brain, GLUT5/Glut5 is expressed in microglia [ 106 ], cerebellar Purkinje cells [ 107 , 108 ], the human BBB [ 103 ], rat hippocampus [ 95 , 109 ], rat cerebral cortex [ 107 , 108 ], rat olfactory bulb [ 108 ], rat optic tract and its terminal fields [ 107 ], and in rat vestibular and cochlear nuclei [ 107 ]. GLUT5 is the sole hexose transporter found in microglia [ 110 ].…”
Section: Fructose Transporters In Choroid Plexus Epithelial Cellsmentioning
confidence: 99%
“…After the acclimatization period, the animals were randomly assigned to either regular or fructose (15% w/v) drinking water. It was previously established that 15% fructose for 3 weeks is a suitable stimulus to elicit metabolic disturbances in rats . At 3 weeks of fructose intervention, all animals were subjected to either sham or fluid percussion injury (FPI).…”
Section: Methodsmentioning
confidence: 99%
“…Chronic feeding with fructose (4–16 weeks) was reported to induce apoptosis, reduce hippocampal neurogenesis [ 13 ], and impair hypothalamic leptin sensitivity [ 14 ], while increasing oxidative stress and neuroinflammation, and causing down-regulation of the cholinergic system in the hippocampus and cerebral cortex of rats [ 15 ]. Interestingly, recent studies have suggested that shorter periods (1–2 weeks) of fructose intake induce autophagy in rat cerebral cortex, reduce both the hippocampal weight and the expression of molecules related to cellular plasticity, and significantly increase markers of inflammation and oxidative damage in young and adult rats [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%